How Public Libraries Help Immigrants Adjust to Life in a New Country: A Review of the Literature. Issue 5 (September 2022) - Grossman, Suzanne; Agosto, Denise E.; Winston, Mark; Epstein, Rabbi Nancy E.; Cannuscio, Carolyn C.; Martinez-Donate, Ana; Klassen, Ann C.
Public library programs and services offer opportunities to help immigrants navigate daily life in unfamiliar surroundings and a new language. For example, language classes address the social determinants of health as they encourage social participation and community ties and help develop friendships. The purpose of this research was to conduct a narrative literature review to understand how immigrants use public libraries and how public library services influence the social determinants of health for immigrant populations. Keyword searches were conducted on five databases to identify research papers that met the inclusion criteria: empirical studies published in English between 2000 and 2020 related to immigrants' use of public libraries. Thirty-one articles were included in the analysis. Thematic coding identified cross-cutting themes within the sample using the framework of the social-ecological model. Immigrants commonly use public libraries for programs (e.g., language learning), collections (e.g., borrowing books), and services (e.g., asking librarians questions). Immigrant patrons often reported satisfaction with library programs, services, and collections in the language of the host country. A frequent criticism was the relevance and accessibility of collections in their heritage language. In addition, library staff demographics often did not reflect those of immigrant patrons. Health-enhancing benefits associated with library use included increased confidence and self-esteem, cultural integration and preservation, trust and relationships (e.g., making friends), community awareness and engagement, and political integration. Future research and practice areas include collaboration between public health and library professionals to develop library programming that maximizes health and well-being among immigrants.